Beneficial effect of consuming milk containing only A2 beta-casein on gut microbiota: A single-center, randomized, double-blind, cross-over study - Chin-Hee Song; Nayoung Kim; Yonghoon Choi; Seulgi Kim; Kyung Su Kim; Min Hee Park; Sang Hee Lee; Dong Ho Lee (PLoS ONE, 2025)
Cow milk contains essential nutrients, with β-casein existing in A1 and A2 forms. Studies suggest that A2 milk (containing only A2 β-casein) may offer gastrointestinal (GI) benefits compared to A1/A2 milk (containing both forms). This study investigated the effects of A2 milk consumption on the gut microbiota of South Korean cohort experiencing GI discomfort after consuming A1/A2 milk. Thirty-five participants with GI discomfort after milk consumption were included. Stool DNA was analyzed using 16S rRNA gene sequencing before and after consuming either A1/A2 or A2 milk. Beta diversity analysis using the generalized UniFrac distance method revealed a significant shift in gut microbiota composition after A2 milk consumption (p = 0.04), but no significant change after consuming A1/A2 milk. Significant differences in gut microbiota composition were found between A1/A2 and A2 milk drinkers after milk consumption (p = 0.031). Alpha diversity indices remained unchanged. Notable increases in beneficial microbes, including Bifidobacterium and Blautia, were observed after A2 milk intake. Linear discriminant analysis Effect Size (LEfSe) analysis identified significant enrichment of Actinobacteria, particularly Bifidobacterium longum and Blautia wexlerae, in the A2 group. Phylogenetic Investigation of Communities by Reconstruction of Unobserved States (PICRUSt) analysis highlighted enriched transport systems related to energy, peptides, sugars, and raffinose family oligosaccharides in the A2 group. Spearman correlation showed significant associations between Bifidobacterium, Blautia, and enhanced transport systems exclusively in the A2 group. Two weeks of A2 milk consumption led to significant alterations in gut microbiota, promoting beneficial microbes and related functions. A2 milk could be a suitable alternative for subjects who experience milk-intake-related GI discomfort.